Omentin inhibits osteoblastic differentiation of calcifying vascular smooth muscle cells through the PI3K/Akt pathway - Duan, Xin-Yun; Xie, Ping-Li; Ma, Yu-Lin; Tang, Si-Yuan (Amino acids, 2011)
Arterial calcification is positively associated with visceral adiposity, but the mechanisms remain unclear. Omentin is a novel adipokine that is selectively expressed in visceral adipose tissue. The levels of circulating omentin are decreased in obesity, and they correlate negatively with waist circumference. This study investigated the effects of omentin on the osteoblastic differentiation of calcifying vascular smooth muscle cells (CVSMCs), a subpopulation of aortic smooth muscle cells putatively involved in vascular calcification. Omentin inhibited mRNA expression of alkaline phosphatase (ALP) and osteocalcin; omentin also suppressed ALP activity, osteocalcin protein production, and the matrix mineralization. Furthermore, omentin selectively activated phosphatidylinositol 3-kinase (PI3K) downstream effector Akt. Moreover, inhibition of PI3K or Akt activation reversed the effects of omentin on ALP activity and the matrix mineralization. The present results demonstrate for the first time that omentin can inhibit osteoblastic differentiation of CVSMCs via PI3K/Akt signaling pathway, suggesting that the lower omentin levels in obese (specially visceral obese) subjects contribute to the development of arterial calcification, and omentin plays a protective role against arterial calcification.